2006
DOI: 10.1021/la0532205
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of Aqueous Micellar Solutions of a Triblock Copolymer of Ethylene Oxide and 1,2-Butylene Oxide:  B10E410B10

Abstract: A triblock copolymer of ethylene oxide and 1,2-butylene oxide, denoted B10E410B10, was prepared by sequential oxyanionic polymerization and characterized by 13C NMR spectroscopy and gel permeation chromatography. Micellization and the formation of micelle clusters in dilute aqueous solution, the latter a consequence of micelle bridging, was confirmed by dynamic light scattering, and average association numbers of the micelles were determined by static light scattering for T = 20-40 degrees C. The frequency dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Mistry et al reported non-single Maxwell relaxation modulus data for relatively high concentration poly(butylene oxide)-(etylene oxide)-(butylene oxide) triblock copolymer solutions [30]. Some shear relaxation modulus data for relatively high concentration HEUR solutions [2,4] also deviate from the single Maxwellian form.…”
Section: B Resultsmentioning
confidence: 99%
“…Mistry et al reported non-single Maxwell relaxation modulus data for relatively high concentration poly(butylene oxide)-(etylene oxide)-(butylene oxide) triblock copolymer solutions [30]. Some shear relaxation modulus data for relatively high concentration HEUR solutions [2,4] also deviate from the single Maxwellian form.…”
Section: B Resultsmentioning
confidence: 99%
“…It is known [17] that the dynamic moduli of solutions of copolymer B 12 E 114 B 12 can be scaled against frequency approximately in the manner defined by Trappe and Weitz for colloid particles, while frequency scans obtained for solutions of copolymer B 10 E 410 B 10 are better modelled by a combination of Maxwell elements with a distribution of relaxation times. [22] The present copolymers with E 227 central blocks represent an intermediate case.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the stability of the micelles of E/B copolymers, and so the extent of micellisation, is much affected by the distribution of Bblock lengths, as discussed previously for BEB copolymers. [22] Micelles (and so gels) of copolymers with alkyl blocks, e.g. HEUR copolymers and poly(oxyethylene) diand mono-alkyl ethers, [16,31] are stable down to low temperatures, a consequence of the high hydrophobicity and the uniformity of their alkyl chains.…”
Section: Concentration and Temperature Dependence Of Modulusmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that for this system the fraction of chains that form micelles increased with increasing temperature so that increasing the temperature is equivalent to increasing the concentration. Mistry et al [36] determined the temperature dependence of the terminal relaxation of transient networks formed by the same triblock copolymer. Surprisingly, they found that the relaxation time increased with increasing temperature, contrary to what was observed for PEO chains end-capped with alkyl chains.…”
Section: Polymers With Two Associative End-blocks (B-a-b)mentioning
confidence: 99%